Analisis Tadribat dalam Buku Silsilah Al-Ta’lim Al-Lughah Al-‘Arabiyah Al-Mustawa Al-Awwal At-Ta’bir - Kurniawan, Ogi; Yasmadi (Universitas Islam Ahmad Dahlan Sinjai, 2024)
This research aims to analyze tadribat (practice) in the genealogy book ta'lim al-lughah al-arabiyah al-mustawa al awwal at-ta'bir using sungkono theory. The method used in this paper is descriptive qualitative, using library research. The results of the research are that there are 211 tadribat in this book, consisting of 127 at-tadribat an-namthiyah, and 83 at-tadribat al-ma'nawiyah and 1 at-tadribat al-ittisholiyah. The practices in this book are also in accordance with some of the principles of training according to the Sungkono perspective, but in some other principles the exercises in this book are not in accordance with the principles of training according to the Sungkono. Among the preparation of exercises in this book that are in accordance with Sungkono theory are that they are relevant to the material presented, challenge students to think and be critical, the presentation is in accordance with the characteristics of each subject and the preparation of exercises in this book that are not in accordance with Sungkono theory are meaningful (useful). , according to students' abilities, the forms vary